Streamlining local behaviour through communication, incentives and control: a case study of local environmental policies in China - Heberer, Thomas (Journal of current Chinese affairs, 2011)
This article describes how China uses evaluation ratings and monitoring as incentives in order to foster the implementation of environmental policies at the local level. It is argued that decentralisation in China leaves room for actors at the local levels to manoeuver and bargain with those on higher levels for flexible adjustment of implementation policies according to local conditions. However, decentralisation is accompanied by significant institutional changes in the structure of intergovernmental communication, incentives and control. Accordingly, decentralisation in China exhibits a specific design which leaves space for divergent local environmental policies while also engendering "grass-roots mechanisms". On the whole, this new institutional setting benefits the implementation of environmental policies. (JCCA/GIGA)